Chapter 11 Social Media and Social Justice Movements After the Diminution of Black-owned Media in the United States - Blevins, Jeffrey (Taylor & Francis, 2018)
This volume gathers scholarship from varying disciplinary perspectives to explore media owned or created by members of the African diaspora, examine its relationship with diasporic audiences, and consider its impact on mainstream culture in general. Contributors highlight creations and contributions of people of the African diaspora, the interconnections of Black American and African-centered media, and the experiences of audiences and users across the African diaspora, positioning members of the Black and African Diaspora as subjects of their own narratives, active participants and creators. In so doing, this volume addresses issues of identity, culture, audiences, and global influence.